Heme Oxygenase-1: An Anti-Inflammatory Effector in Cardiovascular, Lung, and Related Metabolic Disorders - Stefan W. Ryter (MDPI AG, 2022)
The heme oxygenase (HO) enzyme system catabolizes heme to carbon monoxide (CO), ferrous iron, and biliverdin-IXα (BV), which is reduced to bilirubin-IXα (BR) by biliverdin reductase (BVR). HO activity is represented by two distinct isozymes, the inducible form, HO-1, and a constitutive form, HO-2, encoded by distinct genes (HMOX1, HMOX2, respectively). HO-1 responds to transcriptional activation in response to a wide variety of chemical and physical stimuli, including its natural substrate heme, oxidants, and phytochemical antioxidants. The expression of HO-1 is regulated by NF-E2-related factor-2 and counter-regulated by Bach-1, in a heme-sensitive manner. Additionally, HMOX1 promoter polymorphisms have been associated with human disease. The induction of HO-1 can confer protection in inflammatory conditions through removal of heme, a pro-oxidant and potential catalyst of lipid peroxidation, whereas iron released from HO activity may trigger ferritin synthesis or ferroptosis. The production of heme-derived reaction products (i.e., BV, BR) may contribute to HO-dependent cytoprotection via antioxidant and immunomodulatory effects. Additionally, BVR and BR have newly recognized roles in lipid regulation. CO may alter mitochondrial function leading to modulation of downstream signaling pathways that culminate in anti-apoptotic, anti-inflammatory, anti-proliferative and immunomodulatory effects. This review will present evidence for beneficial effects of HO-1 and its reaction products in human diseases, including cardiovascular disease (CVD), metabolic conditions, including diabetes and obesity, as well as acute and chronic diseases of the liver, kidney, or lung. Strategies targeting the HO-1 pathway, including genetic or chemical modulation of HO-1 expression, or application of BR, CO gas, or CO donor compounds show therapeutic potential in inflammatory conditions, including organ ischemia/reperfusion injury. Evidence from human studies indicate that HO-1 expression may represent a biomarker of oxidative stress in various clinical conditions, while increases in serum BR levels have been correlated inversely to risk of CVD and metabolic disease. Ongoing human clinical trials investigate the potential of CO as a therapeutic in human disease.